Effect of glycoluril and its derivatives on the flame resistance and physico-mechanical properties of rubber - Sal’keeva, L. K.; Bakibaev, A. A.; Khasenova, G. T.; Taishibekova, Ye. K.; Sugralina, L. M.; Minaeva, Ye. V.; Sal’keeva, A. K. (Pleiades Publishing, 2016)
The effect of bicyclic bisureas (glycolurils) and their derivatives functionalized with hydroxymethyl, halomethyl, and dimethoxyphoshorylmethyl groups on the flame resistance and physico-chemical properties of synthetic isoprene and divinyl rubbers was studied, and the procedures for preparing these agents were suggested. The rubbers with the addition of the synthesized bicyclic bisureas demonstrated satisfactory levels of flame resistance and physico-mechanical parameters.
Keywords: Rubber; Vulcanization; Rubber Compound; Intumescent Coating; Glycoluril